PENGARUH EMPLOYEE ENGAGEMENT, KOMITMEN ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT. SINAR GRAFINDO - Oky Kurniasari; Heny Kurnianingsih (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This research aims to find out how the impact of employees in the organization's commitment, and job satisfaction on the performance of PT employees. Sinar Grafindo. The samples in this study are 100 respondents, namely employees of PT. Sinar Grafindo. Data capture technique using questionnaire with likert scale measurement. The data analysis used in this study includes research instrument tests, classion assumption tests, and hypothesis tests. The results of the Anova F test (Simultant) show that the calculated F value is 3.979 greater than the table F, which is 2.70 and the significance value is 0.010 less than 0.05. Thus, it means that the variable employee engagement, organizational commitment, and job satisfaction significantly affect employee performance at PT. Sinar Grafindo